Diversity and Status of Bryophytes in Panch Pokhari Region of the Northern Sindhupalchok District of Central Nepal - Pradhan, Nirmala (Journal of Natural History Museum, 2015)
This is the first exploration of bryophytes in Panch Pokhari of Sindhupalchok district of central Nepal vertically ranged from 850 to 4300 m asl. Of the total record of 151 species, 60 species were categorized as rare in status and two species Jamesoniella automnalis (D.C.) Steph. and Campylopus rechardii Brid were recorded as threatened species. J. Nat. Hist. Mus. Vol. 27, 2013: 45-58